Design of Interactive Augmented Reality Learning Media Using theVAKT Approach for Early Childhood Vegetable Recognition - Wahyu Kurnia Dewanto; Zilvanhisna Emka Fitri; Achmad Amreza Alfarit; Arizal Mujibtamala Nanda Imron; Reski Yulina Widiastuti; Ery Setiyawan Jullev Atmadji; Fatimatuzzahra Fatimatuzzahra (Universitas Bumigora, 2026)
Early childhood education requires adaptive media to facilitate cognitive and linguistic development. This study aims to evaluate the integration of the Visual-Auditory-Kinesthetic-Tactile (VAKT) frame work into an Augmented Reality (AR) application for vegetable recognition, balancing technical engineering with user-centric design paradigms. This research used a method developed with Unity and the Vuforia SDK; the application architecture incorporates real-time marker tracking, a dual-language localization database, and automated dynamic scoring algorithms. Usability was quantitatively measured with 12 respondents using the Technology Acceptance Model (TAM) and the System Usability Scale (SUS) frameworks. The results of this research yielded a high TAM utility score of 80.63% andan ”Excellent” (B+) SUS rating. Technically, the system effectively maps software constraints onto cognitive stimuli, utilizing single-story sans-serif typography and high-saturation color rendering to sustain attention and support emergent literacy. While nearly 90% of respondents affirmed the application’s learning efficacy, empirical logs exposed a critical friction point: asynchronous background audio caused sensory overstimulation for 41.67% of users. These findings support the Split Attention Effect theory, suggesting that in AR environments, multi-sensory inputs must be hierarchically ordered to prevent cognitive overload. This study concludes that a synchronous multimodal hierarchy is essential for successful interactive multimedia environments.